Virtual Reality - Singh, Umesh; Sahu, Deepika (International Journal of Computer Sciences and Engineering, 2025)
This thesis is described about VR and functions. virtual reality (VR) is a amazing and interesting topic at the current time. This is not really new. It defines the advantage and disadvantage of VR and uses of VR in various field. Virtual Reality (VR) literally makes it possible to experience anything, anywhere, anytime. It is the immersive type of reality technology and can convince the human brain that it is somewhere it is really not. We discuss here about VR, uses, history, application, advantage , disadvantage of VR.